Initially, Newton defined his second law of motion in terms of the rate of change in an object's momentum:

(Pf -Pi)/t = Fnet

Subsequently he developed the concept further to

(mVf - mVi)/t = Fnet or m(Vf - Vi)/t = Fnet

So, (Vf - Vi)/t = Fnet/m

by defining the...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Initially, Newton defined his second law of motion in terms of the rate of change in an object's momentum:

(Pf -Pi)/t = Fnet

Subsequently he developed the concept further to

(mVf - mVi)/t = Fnet or m(Vf - Vi)/t = Fnet

So, (Vf - Vi)/t = Fnet/m

by defining the rate of change in the velocity as acceleration we get the current form of the second law:

a = Fnet/m

From this we can see that if m is constant then a is directly proportional to Fnet. Increasing Fnet causes an increase in the acceleration.